2D capacitance extraction with direct boundary methods. (September 2015) - Borkowski, M.
Abstract: The paper presents the algorithm of hierarchical capacitance extraction based on direct boundary methods. Three selected methods, i.e. Boundary Element Method, direct Trefftz method (based on TH-complete functions) and regular direct Boundary Element Method (direct Trefftz–Kupradze method), are compared for their effectiveness. The algorithm employs binary tree decomposition of the problem domain. Coupling capacitance matrix is calculated in hierarchical process with simultaneous dynamical updating library with basic element matrices. Numerical examples presented in the paper concern 2D planar transmission line structures composed of isotropic dielectric layers.